2019
DOI: 10.1155/2019/9258075
|View full text |Cite|
|
Sign up to set email alerts
|

Noncoding RNAs Act as Tumor-Derived Molecular Components in Inducing Premetastatic Niche Formation

Abstract: Cancer metastasis has been demonstrated as it is the culmination of a cascade of priming steps. Increasing evidence has shown that tumor-derived molecular components (TDMCs) are known as extra cellular vesicle and nonvesicle factors and serve as versatile intercellular communication vehicles which can mediate signaling in the tumor microenvironment while creating the premetastatic niche. Noncoding RNAs (ncRNAs) as one of the TDMCs have been proved in participating in the formation of the premetastatic niche. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Microvesicles can also be secreted and delivered to recipient cells, inducing them to undergo EMT [ 97 ]. Exosomes and microvesicles are classified as tumor-derived secreted factors (TDSFs), and their role in tumor signaling and metastasis is a topic of research, hopefully leading to new strategies for cancer diagnosis, cancer prognosis, and possibly cancer therapy in the future [ 98 , 99 , 100 , 101 , 102 ].…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…Microvesicles can also be secreted and delivered to recipient cells, inducing them to undergo EMT [ 97 ]. Exosomes and microvesicles are classified as tumor-derived secreted factors (TDSFs), and their role in tumor signaling and metastasis is a topic of research, hopefully leading to new strategies for cancer diagnosis, cancer prognosis, and possibly cancer therapy in the future [ 98 , 99 , 100 , 101 , 102 ].…”
Section: An Overview Of Epithelial-to-mesenchymal Transition and Mese...mentioning
confidence: 99%
“…vii. They greatly influence the preparatory mechanism in the distant organs by the name of pre-metastatic niche which is required for the early colonization of the DTCs (Disseminated Tumor Cells) in cancer [ 149 , 150 ].…”
Section: Mechanisms Of Few Secretory Factors Involved In Breast Cancementioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%